CAMERA ANGLES AS MISE-EN-SCÈNE IN THE WONDERFUL STORY OF HENRY SUGAR - Fathin Aulia Fatharani; Rinda Revanita; Syabrina Sri Sulistyani; Febriani Ahmad (Saksama: Jurnal Sastra, 2026)
This study explores the use of camera angles as integral elements of mise-en-scène in shaping the visual identity of The Wonderful Story of Henry Sugar, a short film directed by Wes Anderson. Rooted in the assumption that all cinematic representations carry expressive meaning, the study investigates how camera angles: eye-level, high-angle, low-angle, bird’s-eye view, and Dutch tilt are contributed to constructing visual narratives and influencing audience perception. Drawing on the theoretical framework of Mise-en-Scène: Within the Image, which defines mise-en-scène as the totality of expressive content within a frame, this research views camera angles not as neutral tools, but as carriers of meaning shaped by compositional choices. The research adopts a descriptive qualitative method through content analysis, closely examining selected scenes from the film by observing the function and impact of specific camera angles in context. The findings demonstrate that eye-level shots dominate Anderson’s style, reinforcing narrative neutrality and intimacy, while high-angle and low-angle shots reflect vulnerability and dominance, respectively. Bird’s-eye views are used to evoke detachment, and Dutch tilts mark psychological tension or narrative shifts. Through symmetrical compositions and careful angle selections, the film establishes a stylized yet emotionally resonant visual language. Ultimately, this study affirms that camera angles, as mise-en-scène components, function beyond visual aesthetics, they serve as narrative devices that shape the viewer’s emotional and interpretive experience, supporting the notion that every element within the frame is a deliberate and expressive cinematic choice.